Desk review explained: Editorial judgement, fit, and publishing (Journal of Applied Learning and Teaching, 2026)
For many authors, the editorial desk seems to be something of a black box. A manuscript is submitted, a period of silence follows, and then a decision arrives. When that decision is a desk rejection, it can feel abrupt, impersonal, or difficult to interpret. For editors, however, the desk review is rarely quick or casual. It is one of the most careful and consequential moments in the publishing process.This Editorial is an attempt to make that moment more visible.Over the past six months, a striking proportion of submissions to the Journal of Applied Learning & Teaching (JALT), approximately 96%, have not progressed beyond initial editorial screening. Stated plainly, that figure can sound discouraging. It may invite assumptions about rising barriers or increasingly narrow definitions of quality. Yet neither explanation reflects what is actually happening at the editorial desk. The purpose of this Editorial is to explain why desk rejection occurs so frequently, how those decisions are made, and what they mean and do not mean for prospective authors. We also describe common pitfalls and make a case for stylish academic writing.